A Glimpse at Bicycle-to-Bicycle Link Performance in the 2.4GHz ISM Band - Santos, Pedro M. (2018)
Bicycle-to-bicycle (Bi2Bi) communication can be implemented by well-established technologies in the 2.4GHz ISM band: IEEE 802.11, Bluetooth or IEEE 802.15.4. These technologies have distinct performance due to different physical and data link layers. In this paper, we characterize the mentioned 2.4 GHz-operating technologies over opportunistic links established between bicycles using commodity hardware. We find that, in Bi2Bi links, Blue-tooth, IEEE 802.11 at 24 Mbit/s, and IEEE 802.11 with automatic rate adaptation can communicate only in the immediate surroundings (under 15m of range), to maxima of 1.5 Mbit/s, 17 Mbit/s and 25 Mbit/s, respectively. IEEE 802.15.4 and IEEE 802.11 at 1 Mbit/s sustain connectivity up to 30 and 40 meters and peak transfer rates of 50 kbit/s and 800 kbit/s respectively. In addition, we observed that, in all measurement scenarios, link performance depended strongly on whether bicycles were approaching or moving away, rather than on whether one was at the front or back of the other.